Clinical and histological study of cold physical plasma jet in treatment of full thickness skin wounds of normal and diabetic dogs - Shatha Mustafa Hashim Al Qaseer,; Serwa Ibrahim Salih,; Mohammed Kammas Khalaf, (Journal of the Pakistan Medical Association, 2024)
Objective: To study the effect of physical plasma jet in treating open wounds in diabetic and non-diabetic dogs. Method: The experimental study was conducted at the College of Veterinary Medicine, University of Baghdad, Iraq, from 20 January, 2020 to 1st May 2020, according to (no. 1364/ P.G), and comprised adult male diabetic and nondiabetic dogs. They were divided into non-diabetic group N and diabetic group D. Each group was further divided into treatment subgroup T and control subgroup C. Each dog was subjected to 4 wounds 3×3cm in size. Homemade helium non-equilibrium atmospheric pressure plasma jet therapy was used for healing purposes. Clinical parameters were evaluated by observation, while histological images were scored based on the semi-quantitative evaluation of histological sections on days 3-, 7- and 21-days post-wound. Data was analysed using SPSS Version 26 with One-way ANOVA for statistical analysis between groups and sub-groups. Results: Of the 24 dogs, 12(50%) were in each of the two groups, which were further divided into subgroups having 6(50%) dogs each. The therapy accelerated the process of wound healing in the NT and DT subgroups compared to NC and DC. Clinical observations revealed early and complete closure of plasma-treated wounds in NT and DT subgroups started at day 30 post-wounding, while in the NC subgroup it started at day 35, and in the DC subgroup, wounds failed to close even after 35 days post-wounding. Histological analysis suggested that a plasma jet supported epithelisation, angiogenesis, formation of new hair follicles and collagen fibres, while it also controlled inflammation. In addition, in NT and DT subgroups, it increased the proliferation of fibroblasts and deposition of collagen, and there is a very, highly significant difference between groups (P<0.001), and a significant difference between days (P<0.05). Conclusions: Home-made helium non-equilibrium atmospheric pressure plasma jet therapy improved the quality and pace of wound healing. Key Words: Helium, Hair Follicle, Wound Healing, Collagen, Diabetes, Inflammation, Fibroblasts, Proliferation, Angiogenesis